Information Design and Digital Curation at the Museum of the Person: Folksonomy Converged to the Social Technology of Memory - de Oliveira Souza, Gabriela; Vicentini Jorente, Maria José (The Canadian Journal of Information and Library Science / La Revue canadienne des sciences de l’information et de bibliothéconomie)

(untitled) (Canadian Association for Information Science - Association canadienne des sciences de l'information, 2024)
Web 2.0 has presented challenges and possibilities for cultural facilities and information professionals. Thinking strategically about such aspects implies creating openings for the collaboration of communities of interest in the identification of informational objects, and converging concepts, methodologies and techniques of information design, digital curation and folksonomy, which would address the challenges that emerge in the process of digitization-virtualization and availability of collections on the Web. Given this, cultural facilities must get closer to the communities of interest, as is done by the Museum of the Person (Museu da Pessoa), a digital-virtual and collaborative museum whose collection is composed of life stories. The museum uses the social technology of memory, a methodology that consists of a set of practices, concepts and principles essential for diverse communities of interest and institutions to take ownership of the production and recording of narratives. The present study asks how folksonomy, seen as a resource of information design and digital curation, can converge to the social technology of memory? Thus, the objective is to analyze the possibilities of convergence of folksonomy, information design, and digital curation to the social technology of memory. The specific objectives are to study the main concepts of folksonomy in the context of information design and digital curation, analyze the social technology of memory, and identify possible convergences of folksonomy in methodology. The methodology applied in the present study is theoretical, exploratory, and qualitative, and the method applied was design thinking.